The Determinants of Manufacturer Firm Value in the Indonesia Stock Exchange During Pandemic: Signalling Theory Perspective - Yulianti, Vista; Dian Sulistyorini Wulandari; Yancy (Indonesian Journal of Economic & Management Sciences, 2024)
The importance of a company's value cannot be overstated as it directly correlates with the prosperity of shareholders. Elevated company value translates to increased shareholder wealth, primarily manifested through higher stock prices. This research endeavors to empirically assess the impact of liquidity, leverage, and profitability – independent variables – on firm value within the food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. Employing a quantitative approach, secondary data from the official website (www.idx.co.id) was utilized, encompassing companies within this subsector. The research employed purposive sampling, selecting 28 companies from a total population of 84. Statistical Product and Service Solution (SPSS) version 23 facilitated data analysis using multiple linear regression. Findings revealed that liquidity (X1) exhibited a significance value of 0.511, surpassing the 0.05 significance level (0.511 > 0.05), with a negative t value of -0.663. This implies that liquidity (X1) does not exert a significant influence on firm value (Y). Likewise, leverage (X2) yielded a significance value of 0.326, exceeding the 0.05 level (0.326 > 0.05), accompanied by a positive t value of 0.993